(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2018)
The Commission Delegated Regulation (EU) no. 2018/1629 modifies the list of animal diseases included in Annex II to Regulation (EU) no. 2016/429. In the present work, the Authors compare the legislative developments regarding Animal Health from D.P.R. n. 320/54 to Reg. (UE) n. 2016/429 and to Delegated Reg. (EU) n. 2018/1629, highlighting the consequences of application regarding the notifiable diseases